The history of families at-risk for hereditary breast and ovarian cancer: what are the impacts of genetic counseling and testing? - Campacci, Natalia; Grasel, Rebeca Silveira; Galvão, Henrique de Campos Reis; Garcia, Lucas França; Ribeiro, Paula Carvalho; Pereira, Kercy Fram de Jesus de Sena; Goldim, José Roberto; Ashton-Prolla, Patricia; Palmero, Edenir Inêz (Frontiers in Psychology, 2024)
We assessed the effects of cancer genetic counseling (CGC) and genetic testing (GT) on women affected by cancer who are at risk for hereditary breast and ovarian cancer predisposition syndrome (HBOC). This study encompasses four time points: before the CGC session, after the CGC session when blood is drawn for GT, after disclosure of GT results, and six months following disclosure of GT results. The impacts of CGC and GT were assessed using psychosocial questionnaires. Additionally, a pedigree, genogram, and ecomap were constructed through a semistructured interview. A total of sixty women were included in the study. Most participants considered their perception of cancer risk to be equivalent to that of the general population, even among those with pathogenic variants.An increased perception of breast and ovarian cancer risks was associated with a heightened inclination toward religious engagement as a coping mechanism. Patients carrying variants of uncertain significance expressed greater concerns about developing another cancer compared to those who had BRCA1 and BRCA2 wild type or pathogenic variants.Qualitative analysis of the genograms and ecomaps demonstrated that the CGC/GT processes facilitate communication within families. The genogram analyses revealed the impact of CGC and GT processes on families at risk for hereditary cancer. Changes in some family relationships were observed, and an improvement in communication was noted following the GT process.